2018
DOI: 10.1111/1756-185x.13409
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence and correlates of osteoporosis in men aged 50  years and over: A nationwide osteoporosis survey in Taiwan

Abstract: Aims Osteoporosis is one of the consequences of aging, and it remains underdiagnosed and undertreated; this study aimed to present the characteristics and prevalence of osteoporosis in elderly men by conducting a nationwide survey in Taiwan. Methods The participants were enrolled between 2008 and 2011, and bone mineral density (BMD) was measured via dual‐energy X‐ray absorptiometry for the hip (total), lumbar spine (L1‐4), and femoral neck (FN). Patients with rheumatoid arthritis, female patients, and those us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…This increase may be related to a decrease in postmenopausal estrogen in women [ 13 ]. A history of fractures is the most important risk factor for osteoporosis in men [ 15 ]. Men generally have more bone mass and content than women.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This increase may be related to a decrease in postmenopausal estrogen in women [ 13 ]. A history of fractures is the most important risk factor for osteoporosis in men [ 15 ]. Men generally have more bone mass and content than women.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of osteoporosis increases with age. People with osteoporosis were significantly older [ 13 , 15 , 21 , 62 , 63 ], had lower body weight, shorter height, and more previous fractures than people without osteoporosis [ 15 ]. The highest rate of bone loss occurs after the age of 65 [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…В исследовании NHANES (National Health And Nutrition Examination Survey) в общей популяции в возрастной группе от 70 до 79 лет распространенность остеопороза составила 16,4%, в возрастной группе 80 лет и старше достигала 26,2% [21]. В исследовании, проведенном среди мужчин в Тайване в возрасте 70±9,3 года, распространенность остеопороза составила 9,7% [22]. В то же время исследование в США в сходной возрастной группе (от 65 до 99 лет) продемонстрировало распространенность остеопороза до 24% [23].…”
Section: статистический анализunclassified
“…Based on an analysis of the Taiwan’s population-based National Health Insurance claims database, the prevalence of osteoporosis for males in 2013 was 1,400 and 6,227 per 100,000 persons in those aged 60–69 years and ≥80 years, respectively (Wang et al, 2017). A nationwide osteoporosis survey conducted in Taiwan reported that the prevalence of male osteoporosis was 9.7%, and the factors associated with male osteoporosis were aging, lower body weight, and a history of fracture (Ko et al, 2018). In Taiwan, osteoporosis in men is still underrecognized and undertreated.…”
mentioning
confidence: 99%